2015
DOI: 10.1007/s10551-015-2885-9
|View full text |Cite
|
Sign up to set email alerts
|

Leading by Example: Values-Based Strategy to Instill Ethical Conduct

Abstract: 1 ) The authors contributed equally to this research and are listed alphabetically.Leading by example; Values-based strategy to instill ethical conduct. AbstractYears of research clearly shows that relying on traditional organizational power bases is not effective when companies want to promote business ethics and performance. It is not only that the use of legitimate power to establish ethics codes and coercive power to punish employees who do not comply does not work; this study -based on a multi-method rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 21 publications
1
9
1
1
Order By: Relevance
“…Such proactive awareness and capacity for action does not end with the focal firm and its management but also extends to its stakeholders where active monitoring and close interaction enables the firm to become a positive influence on these stakeholders. This is in line with the notion of values‐based leadership proposed by Nygaard, Biong, Silkoset, and Kidwell (). For mindful organizations, a rich and proactive awareness of environmental vulnerability and resources unsustainability, and the capacity for action engenders designing strategies for preempting and forestalling such vulnerabilities, for example, green sourcing, green logistics, environmentally friendly product design and packaging, reusable ampules, high productivity in energy and water consumption and waste generation and recycling, mindful post‐consumption waste disposal, and generic consumer (environmental) education and enlightenment.…”
Section: Introductionsupporting
confidence: 89%
“…Such proactive awareness and capacity for action does not end with the focal firm and its management but also extends to its stakeholders where active monitoring and close interaction enables the firm to become a positive influence on these stakeholders. This is in line with the notion of values‐based leadership proposed by Nygaard, Biong, Silkoset, and Kidwell (). For mindful organizations, a rich and proactive awareness of environmental vulnerability and resources unsustainability, and the capacity for action engenders designing strategies for preempting and forestalling such vulnerabilities, for example, green sourcing, green logistics, environmentally friendly product design and packaging, reusable ampules, high productivity in energy and water consumption and waste generation and recycling, mindful post‐consumption waste disposal, and generic consumer (environmental) education and enlightenment.…”
Section: Introductionsupporting
confidence: 89%
“…This study also accepts Mohamed et al [2] research findings, which confirmed that the success of ethical values teaching in educational institutions is performed in three processes: knowledge, habits, and attitude. Besides, this study rejects research that says that traditional organizational power bases are not effective in promoting organizational ethics and performance [58].…”
Section: The Strategies For Values Cultivation Figure 2 Model Of Valcontrasting
confidence: 77%
“…Rao (2017) explores leadership based on principles, values, and morals, suggesting valuesbased leadership is built upon integrity, transparency, ethical considerations, and a focus on "what is right" (p. 2). Nygaard, Biong, Silkoset, and Kidwell (2017) suggest values-based leadership has the potential to influence employees' ethical attitudes and behaviors, "leadership by role model, 'the good example' or 'the good shepherd' (known as referent power), is the best way to support and promote ethical values… far better than forcing the effect" (p. 134). These assertions provoke further exploration of potential connections between values-based leadership theories, well-being, and the emerging profound leadership theory.…”
Section: Problem Statementmentioning
confidence: 99%